Dominant and Recessive Major R Genes Lead to Different Types of Host Cell Death During Resistance to Xanthomonas oryzae in Rice - Cao, Jianbo; Zhang, Meng; Xiao, Jinghua; Li, Xianghua; Yuan, Meng; Wang, Shiping (Frontiers in Plant Science, 2018)
The bacterial blight caused by Xanthomonas oryzae pv. oryzae (Xoo) is the most devastating bacterial disease of rice worldwide. A number of dominant major disease resistance (MR) genes and recessive MR genes against Xoo have been cloned and molecularly characterized in the last two decades. However, how these MR genes mediated-resistances occur at the cytological level is largely unknown. Here, by ultrastructural examination of xylem parenchyma cells, we show that resistances to Xoo conferred by dominant MR genes and recessive MR genes resulted in different types of programmed cell death. Three dominant MR genes Xa1, Xa4, and Xa21 and two recessive MR genes xa5 and xa13 that encode very different proteins were used in this study. We observed that Xa1-, Xa4- and Xa21-mediated resistances to Xoo were associated mainly with autophagy-like cell death featured by the formation of autophagosome-like bodies in the xylem parenchyma cells. In contrast, the xa5- and xa13-mediated resistances to Xoo were associated mainly with vacuolar-mediated cell death characterized by tonoplast disruption of the xylem parenchyma cells. Application of autophagy inhibitor 3-methyladenine partially compromised Xa1-, Xa4-, and Xa21-mediated resistances, as did Na2HPO4 alkaline solution to xa5- and xa13-mediated resistances. These results suggest that autophagy-like cell death is a feature of the dominant MR gene-mediated resistance to Xoo and vacuolar-mediated cell death is a characteristic of the recessive MR gene-mediated resistance.